ANALISIS KOMPARATIF MANAJEMEN POAC, POLA PEMBELAJARAN DAN EVALUASI INPUT-PROSES-OUTPUT ANTARA SDN 01 TELUK BATANG DAN SD MUHAMMADIYAH 1 PONTIANAK - Megasari, Rini (FKIP UM Pontianak, 2026)
This research is motivated by the significant quality gap between elementary schools in Pontianak City, particularly between SDN 01 Teluk Batang, categorized as an underdeveloped school, and SD Muhammadiyah 1 Pontianak, categorized as a more advanced school. This gap is evident in various indicators of learning achievement, accreditation, and school reputation, yet it has not been extensively studied comparatively in managerial and pedagogical aspects. The main problem of this research is how the differences in school management (POAC), learning patterns, and evaluation systems between the two schools contribute to the quality gap. This research employs a qualitative approach with a comparative study design, where data were collected through passive participatory observation, semi-structured interviews, and document analysis. The results show that SD Muhammadiyah 1 Pontianak significantly excels in all three aspects with an average score of 90.0, while SDN 01 Teluk Batang only achieves 42.3, with the largest gap found in the learning pattern aspect (52 points). The unique finding of this research is the revelation of systemic interconnections between management, learning, and evaluation that form a continuous improvement cycle in the advanced school, while the underdeveloped school lacks such mechanisms. This research recommends the need for simultaneous intervention in all three aspects and affirmative policies from the Education Office to address the quality gap among elementary schools.